High removal of chlorinated solvents by reusable polydimethylsiloxane based absorbents. Issue 2 (1st December 2022) - Saleh Medina, Leila M.; Cánneva, Antonela; Molinari, Fabricio N.; D'Accorso, Norma; Negri, R. Martín
Abstract: The objective of this work is to prepare absorbent materials based on polydimethylsiloxane (PDMS) for the absorption of organic solvents by a relative simple method, with large absorption capacities and reusability. Different particles (ZnO, MgSO4, ZnCl2, and NaHCO3 ) were first incorporated in PDMS and then removed by immersion in HCl (c) or water. The absorbent materials were characterized by TGA, mercury porosimetry, stress–strain curves, SEM, EDS, XPS, FTIR, and water contact angle. The materials can absorb polar organic chlorinated solvents (carbon tetrachloride, dichloroethene, dichloromethane, and chloroform) more than four times its own weight. Other solvents were also tested showing 2–3 times its own weight. Additionally, these materials show demulsification properties and absorption of oleophilic compounds. The reusability of the material makes them good candidates for remediation of polluted water. Abstract : Preparation and application of PDMS based sponges.